2018
DOI: 10.3390/genes9030172
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Surface Layer Glycoproteins and Genes Involved in Protein Glycosylation in the Genus Haloferax

Abstract: Within the Haloferax genus, both the surface (S)-layer protein, and the glycans that can decorate it, vary between species, which can potentially result in many different surface types, analogous to bacterial serotypes. This variation may mediate phenotypes, such as sensitivity to different viruses and mating preferences. Here, we describe S-layer glycoproteins found in multiple Haloferax strains and perform comparative genomics analyses of major and alternative glycosylation clusters of isolates from two coas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 77 publications
(107 reference statements)
0
19
0
Order By: Relevance
“…In Haloferax species, there are two pathways which control glycosylation of external features. One is relatively conserved and could have functions other than virus avoidance, while the other is highly variable and shows hallmarks of having genes mobilized by horizontal transfer [85]. At least one halovirus has been found to require glycosylation by its host in order to infect properly [86].…”
Section: Discussionmentioning
confidence: 99%
“…In Haloferax species, there are two pathways which control glycosylation of external features. One is relatively conserved and could have functions other than virus avoidance, while the other is highly variable and shows hallmarks of having genes mobilized by horizontal transfer [85]. At least one halovirus has been found to require glycosylation by its host in order to infect properly [86].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, only recently, S-layer glycoproteins of hyperthermophilic archaea have been shown to accumulate iron and sulfur from the environment 27,28 . Also, recent studies revealed S-layer glycosylation to be crucial for cell-to-cell interactions during the mating process of the archaeon Haloferax 29 and comparative genomics suggest a within-niche variation of glycosylation enabling Haloferax to discriminate between such mating partners and also viruses 30 . Similarly, virus-host interaction between Halorubrum sp.…”
mentioning
confidence: 99%
“…The levels of expression of many of the genes in the low salt glycosylation pathway increased even though the mating was performed in salinities above “optimal” in the mating studies by Shalev et al, and well above the concentrations used in the “low salt” conditions 19 . While, expression of low salt glycosylation machinery under conditions of normal salinity have been previously observed 60 , in this case the initiation of the pathway could be in response to perturbation of the cell membrane, whether caused by decreased salinity or other potential stresses, such as viral infection 21 . One explanation for our transcript data would be that the formation of cytoplasmic bridges connecting cell envelopes during mating may be an additional membrane stress factor affecting “low salt” glycosylation gene synthesis.…”
Section: Resultsmentioning
confidence: 83%
“…volcanii DS2 expresses different S-layer glycosylation when required to grow at lower-than-optimal salinity 20 , and these pathways are constructed uniquely amongst individual Hfx. volcanii strains that are identical for their rpoB gene 21 . Such variance of S-layer glycosylation patterns implies an impact on self-recognition even within species.…”
Section: Introductionmentioning
confidence: 99%